Trends in water quality in a subtropical Australian river-estuary system: Responses to damming, climate variability and wastewater discharges. (1st September 2020) - Eccles, Rohan; Zhang, Hong; Hamilton, David; Maxwell, Paul
Abstract: The Logan-Albert estuary in southeast Queensland, Australia, has high biodiversity and supports multiple economic and recreational services. Elevated nutrient and sediment loads have been a longstanding management issue for the estuary. We investigated the spatial and seasonal patterns of nutrients and turbidity along the Logan-Albert estuary and assessed the effects of a recently constructed upstream dam. Nutrient concentrations and turbidity levels were analysed using 15 years of monitoring data from 19 water quality sites throughout the estuary. We hypothesised that the construction of Wyaralong Dam would act as a nutrient and sediment sink which may have positive effects on downstream water quality. Long-term trends of water quality constituents were evaluated using a non-parametric seasonal Mann-Kendall test and the effect of upstream impoundment was assessed with a Before-After Control-Impact (BACI) test. Nutrient concentrations and turbidity levels declined significantly with time in the upper Logan estuary and, to a lesser extent, in the lower Albert estuary. The general improvement of water quality in the upper Logan estuary was attributed to construction of the Wyaralong Dam. Significant decreases in concentrations of total phosphorus (TP) and oxidised nitrogen (NOx -N) along the lower Albert were principally attributed to wetter conditions over the 15-year dataset, which diluted point-source loads from a nearby wastewater treatment plant (WWTP). Our results show that estuarine water quality changes can be highly dynamic with interactions amongst climate and management practices that necessitate long-term monitoring programs with good spatial coverage. Highlights: Water quality trends and impact of a constructed dam were assessed Dam impoundment found to reduce nutrients and turbidity in a subtropical estuary Dry periods led to a build-up of nutrients and turbidity around treatment plants Wetter conditions help dilute point loads from wastewater treatment plants Climatic and management factors often act synergistically